Mutations, evolutionary theory and cancer. - Tomlinson, I (1993)
When searching for mutations that may be responsible for tumourigenesis and interpreting their significance, molecular oncologists often make a number of implicit assumptions about how and why tumour genotypes develop. These assumptions are based on an underlying classical model of tumourigenesis. The classical model has a number of similarities to models of evolution: given the parallels between the growth of tumours and the evolution of whole organisms, this is to be expected. However, consideration of tumourigenesis as an evolutionary process also suggests some modifications that might be made to the classical model. The experimental methods and data analysis of molecular oncology must take full account of the potential contribution of evolutionary theory. As the study of mutations in cancer expands, molecular oncologists are starting to do this.